German universities seek to reclaim lost glory. - Blau, J.
German universities were originally designed to train members of an ultra-elite cadre to become teaching researchers. Despite a professional style that was somewhat authoritarian and pompous, the system was generally collegial, informal, and open. This would have been all well and good if the university system had changed to meet new needs. In this paper, the author proposes a reform that promotes a class of super-elite schools. The German universities moves to an undergraduate-graduate-postgraduate systems by 2010 to make it easier for students to transfer credits and degrees within Europe and to allow students seeking training for a profession to receive a degree within three to four years rather than five or six.
Keywords: German university system; Engineering education; Professional education; Undergraduate-graduate-postgraduate system